Cordial Labeling of the Line Graph of Bistar - Bosmia, M. I.; Patel, M. A.; Parmar, Y. M.; Vihol, P. L. (Communications in Mathematics and Applications, 2025)
A binary vertex labeling \(f\) of a graph \(G\) is called a cordial labeling if \(|v_f(0)-v_f(1)| ≤ 1\) and \(|e_f(0)-e_f(1)| ≤ 1\). A graph which admits cordial labeling is called a cordial graph. In this paper, the necessary and sufficient conditions for the line graph of bistar \(B_{n,p}\) to be cordial when \(p=n+4m\) and \(p=n+4m+2\) where \(m\in \mathbb{N}\cup \{0\}\) are discussed.
Keywords: Line graph; Bistar; Cordial labeling